Trade-up and trade-down: models for capturing change in consideration set - Garratt, Mark (Henry Stewart Talks, 2010)
Pricing issues that arise in categories where there are differences in quality, Introduction to a methodology for understanding budget constraints, price-value of product attributes and price power of superior goods, Case studies in health and beauty, and consumer electronics categories, Comparison to results obtained from standard choice and conjoint methods